New records of long-legged flies (Diptera, Dolichopodidae) from Central and North-Eastern Iran - I. Ya. Grichanov; A. Ahmadi; O. E. Kosterin (Acta Biologica Sibirica, 2017)
During a 2016-2017 survey conducted in Isfahan, Lorestan, Markazi, North Khorasan, Razavi Khorasan, South Khorasan and Tehran provinces located in the Central and North-Eastern Iran, about 1000 specimens of Dolichopodidae were collected and identified. Eight dolichopodid species [Dolichopus jaxarticus Stackelberg, 1927, Hydrophorus viridis (Meigen, 1824), Medetera diadema (Linnaeus, 1767), M. lamprostoma Loew, 1871, M. roghii Rampini et Canzoneri, 1979, Tachytrechus kowarzi Mik, 1864, Tachytrechus sogdianus Loew, 1871, and Thinophilus flavipalpis (Zetterstedt, 1843)] are recorded for the first time in Iran. Dolichopus subimmaculatus Kazerani, Pollet, Khaghaninia, 2017, is placed in synonymy with Dolichopus perversus Loew, 1871 (syn. nov.). Lectotype is designated for D. perversus.